Outcomes and complications of shoulder arthroplasty in patients with celiac disease: A large insurance claims matched cohort analysis - Camden Bohn; Catherine Hand; Chase Gornbein; Harmanjeet Singh; Daanish Khazi-Syed; Josh Chang; Brian Forsythe (Journal of Orthopaedic Reports)
Introduction: Celiac disease (CD) is an autoimmune enteropathy with systemic effects, including impaired bone and joint health. While CD has been linked to adverse outcomes in lower extremity arthroplasty, its impact on shoulder arthroplasty remains unexplored. This study aims to characterize postoperative outcomes and complications in CD patients undergoing shoulder arthroplasty, hypothesizing that CD patients will experience higher complication rates compared to matched controls. Methods: A retrospective matched cohort analysis was conducted using the PearlDiver national insurance claims database. Patients who underwent primary anatomic, reverse, or hemiarthroplasty between 2010 and 2020 were identified. CD patients were matched 1:2 to controls based on age, sex, and Elixhauser Comorbidity Index (ECI). Primary outcomes included revision arthroplasty and rotator cuff repair (RCR). Secondary outcomes encompassed 90-day complications, including infections, emergency department (ED) visits, acute kidney injury, pneumonia, pulmonary embolism, and urinary tract infection. Multivariate regression analysis was performed to adjust for confounders. Results: Among 191,178 shoulder arthroplasty patients, 739 (0.4 %) had CD. The final cohorts included 733 CD patients and 1460 matched controls. CD patients had significantly higher odds of 90-day complications, including infection (OR 2.7, p < 0.001), ED visits (OR 2.4, p < 0.001), acute kidney injury (OR 2.1, p = 0.006), pneumonia (OR 2.6, p < 0.001), pulmonary embolism (OR 5.4, p < 0.001), and urinary tract infection (OR 3.8, p < 0.001). However, revision arthroplasty (OR 0.9, p = 0.572) and post-arthroplasty RCR rates (OR 1.1, p = 0.606) were comparable between groups. Conclusion: CD is associated with an increased risk of short-term complications following shoulder arthroplasty but does not appear to influence revision or RCR rates. These findings highlight the need for heightened perioperative vigilance in CD patients undergoing shoulder arthroplasty to mitigate potential complications.